Enhancing Reading Comprehension Skill Through Retelling Story - Dindadari Arum Jati; Nandy Intan Kurnia; Regita Sekar Arrum (English Education and Literature Journal (E-Jou), 2026)
English reading comprehension remains a challenge for many Indonesian students learning English as a foreign language. This study investigates the use of story retelling as a pedagogical strategy to improve students’ reading comprehension. Conducted in 2021, the study employed a descriptive quantitative approach with a one-group pre-test and post-test design involving nine Grade XII students from an Islamic private senior high school in Yogyakarta, Indonesia, who followed the 2013 national curriculum. The students read two Aesop’s fables, The Boy Who Cried Wolf and The Fox and the Grapes, and retold the stories through written and recorded oral tasks as part of emergency remote teaching during the COVID-19 pandemic. Students’ performances were assessed by three teachers using a scoring rubric covering relevancy, accuracy, fluency, and creativity, with relevancy and accuracy treated as the primary indicators of reading comprehension. Data were analyzed through descriptive comparison of mean pre-test and post-test scores. The results indicate an overall improvement in students’ reading comprehension, particularly in terms of relevancy and accuracy in the post-test. These findings suggest that story retelling can serve as an effective instructional strategy to support reading comprehension in English, especially when integrated with written and oral activities. This study highlights the potential of children’s literature, such as Aesop’s fables, to facilitate comprehension among Indonesian senior high school students